Long-term prognostic value of stress CMR-related coronary revascularization to predict death: a large registry with > 200, 000 patient-years of follow-up. (13th July 2021) - Pezel, T; Unterseeh, T; Garot, P; Hovasse, T; Sanguineti, F; Toupin, S; Morisset, S; Champagne, S; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: While the benefit of coronary revascularization in patients with stable coronary artery disease (CAD) is debated, data assessing the potential interest of stress CMR to guide coronary revascularization are limited. PURPOSE: To assess the long-term prognostic value of stress CMR-related coronary revascularization in consecutive patients from a large registry. METHODS: Between 2008 and 2018, a retrospective cohort study with a median follow-up of 6.0 years (interquartile range: 5.0-8.0) included all consecutive patients referred for stress CMR. Stress CMR-related coronary revascularization was defined by any coronary revascularization performed within 90 days after CMR. The primary outcome was all-cause death based on the electronic National Death Registry. RESULTS: Among the 31, 752 consecutive patients (mean age 63.7 ± 12.1 years and 65.7% males), 2, 679 (8.4%) died at 206, 453 patient-years of follow-up. Inducible ischemia and late gadolinium enhancement (LGE) by CMR were associated with death (both p < 0.001). In multivariable Cox regression, inducible ischemia and LGE were independent predictors of death (HR = 1.61; 99.5%CI 1.41-1.84; HR = 1.62; 99.5%CI 1.41-1.86, respectively; p < 0.001). CMR-related coronary revascularization was an independent predictor of greater survival (HR: 0.66; 99.5%CI: 0.52-0.84; p < 0.001). CMR-related revascularization was associated with a lower incidence of death in patients with severe inducible ischemia (p < 0.001), but showed no benefit in patients with mild or moderate ischemia (p = 0.109). CONCLUSIONS: In this large observational series of consecutive patients, stress perfusion CMR had important incremental long-term prognostic value to predict death over traditional risk factors. CMR-related revascularization was associated with a lower incidence of death in patients with severe ischemia.